Comparability of blinded remote and site-based assessments of response to adjunctive esketamine or placebo nasal spray in patients with treatment resistant depression. (April 2019) - Targum, S.D.; Daly, E.; Fedgchin, M.; Cooper, K.; Singh, J.B.
Abstract: Functional unblinding due to treatment emergent adverse events (TEAEs) may occur with any investigational drug and poses a challenge for double-blind, placebo-controlled studies. This pilot study compared site-based Montgomery-Asberg Depression Rating Scale (MADRS) scores to remote, site-independent scores by blinded raters. Audio-digital recordings of site-based MADRS interviews were obtained from a subset of patients during a double-blind, placebo-controlled study of esketamine nasal spray or placebo spray in treatment resistant depression (Clinical Trials Registration:NCT01998958 ). Fourteen of 67 patients (21%) in the ITT population were randomly selected from 3 clinical trial sites. The site-based MADRS interviews were recorded at the baseline and 2 h post-dose assessments on the first intranasal dosing day. Site-independent raters scored the recordings and were blinded to treatment and all reported TEAEs, including any transient dissociative/perceptual symptoms. None of the 7 placebo-assigned patients achieved a treatment response or remission at the 2-h post-dose assessment. Four of the 7 esketamine-assigned patients (57.1%) achieved a treatment response at 2-h post-dose, and 3 patients (42.9%) achieved remission. Three esketamine-treated patients experienced transient dissociative symptoms. The remote site-independent raters essentially replicated the site-based MADRS scores and yielded a 92.9% predictive value for matching treatment response and remission rates. This small pilot study affirms that blinded remote ratings (without the likelihood of functional unblinding) are comparable to site-based ratings of efficacy of esketamine nasal spray. The audio-digital recording method offers a reasonable strategy for other studies that may also be vulnerable to functional unblinding due to distinctive TEAEs. Highlights: Functional unblinding is a potential ratings issue after esketamine administration. In this pilot study, blinded, remote MADRS ratings replicated site-based scores. Remote ratings yielded very high predictive values for response and remission rates.